Efeito da ingestão de castanha de caju sobre parâmetros físicos, bioquímicos e comportamentais em ratos dislipidêmicos - Dias, Celina de Castro Querino (2021)
A cashew nut is a fruit with an excellent nutritional profile, rich in unsaturated fats and antioxidant compounds, which can be used in the treatment of dyslipidemia and behavioral disorders. Being, the etiology of dyslipidemia is the regular consumption of a diet rich in fat and, it is known that this is also related to oxidative stress, which can cause neurological disorders, such as anxiety. Dyslipidemia is a risk factor associated with the development of cardiovascular diseases, in some cases, and can be treated through dietary changes. This study aimed to evaluate the effect of cashew nut supplementation on biochemical, murinometric and behavioral parameters in dyslipidemic rats. For this, Wistar rats were randomly assigned to three groups (n = 10): Control (CONT), Dyslipidemic (DL) and Dyslipidemic Cashew Nut (DLCN). The DL and DLCN groups underwent dyslipidemia induction at the beginning of the experiment. The post-induction DLCN group was treated for 28 days with supplementation of 1g of roasted cashew nuts. The following were adopted: body weight, feed intake, body mass index, waist and chest circumference, blood glucose, plasma lipid profile, fats: visceral, fecal and liver; fatty acid profile: liver, fecal and brain, in addition to anxiety-like behavior through the open field testicles and elevated plus-maze. The results of the biochemical parameters obtained showed a significant increase (p < 0.05) in the HDL index of the DLCN group compared to the DL group, there was a reduction in food consumption, a reduction in visceral fats, an increase in plasma triglycerides (p < 0.05), impaired glycemic metabolism and increased liver fat (p < 0.05). The result of the behavioral tests indicated an anxiolytic effect for the DLCN group, which had a higher number of breeding, less preparation time in the open field, and more time in the open arms and in the central area of the labyrinth. Therefore, a cashew nut supplementation associated with maintaining a high-fat diet is unable to improve dyslipidemia, and is not able to convert all the damage caused, causing glycemic changes and accumulation of liver fat. However, with the results, an anxiolytic effect in animals treated with cashew nuts was forgotten. It is concluded that the cashew nut supplementation may have a reduction in its functional potential when associated with the maintenance of a diet rich in fat, even though it is a fruit source of antioxidants and unsaturated fats.